Factors Influencing the Income of Urban Informal Workers: Evidence from Nepal - Adhikari, Dipak Bahadur (Economic Journal of Development Issues, 2020)
Due to lack of formal job and flexible nature of informal work, large number of workers are attracted into the informal sector in developing countries. The paper examines the case of urban Nepal to study the impact of informal sector in the incomes and livelihood of such workers. This paper is based on cross-sectional data that was collected in 2020 in all six metropolitan cities of Nepal. The fixed income determination multiple regression model focuses on how the income of informal workers have been affected by various choice variables. Mostly, people of prime working age and early working age are involved in this sector. The empirical results show that the average annual earnings of the respondents was very close to national minimum wage. Most of the selected explanatory variables were significant with positive sign associated with higher level of annual income.